Multi-layer-combination method to retrieve high-temperature spectral properties of C-plane sapphire. (June 2018) - Zhang, Shun-De; Sun, Feng-Xian; Xia, Xin-Lin; Sun, Chuang; Ruan, Li-Ming
Highlights: A Multi-Layer-Combination (MLC) method to enhance the difference of transmittance is proposed. The transmitted nature of MLC slabs of C-plane sapphire was generalized. High-temperature spectral properties were retrieved from transmittance data. Abstract: For high transparent materials, the difference among the transmittances of various slabs in different thicknesses is very slight since the index of absorption is rather small. However, the divergence of transmittances is very necessary to provide multiple independent constraints for retrieving spectral intrinsic properties from transmitted data with an acceptable accuracy. A Multi-Layer-Combination (MLC) method in which multiple sheets compose a transmitted combination is proposed to provide obviously different transmittances. In this study, the measurements on MLC slabs of C-plane sapphire were performed between 0.8 and 7.0 µm from room temperature to 1800 K. For a given total thickness, the measured results show that the stacking structure of multiple layers can obviously diminish the transmittance, but has no influence on the infrared cutoff and infrared border of high transparency. The spectral refractive indexes and absorption indices within 0.8–5 µm were extracted from transmittance data by minimizing the standard deviation between measurements and predictions. The results indicate that all the properties are wavelength dependent and temperature dependent. Spectral refractive indexes rise regularly with growing temperature and decrease slowly with increasing wavelength. For a researched temperature, the index of absorption levels off in the high transparent interval and climbs steadily in the next spectrum as the wavelength increases. In the tested temperature range of 300–1800 K, the spectral absorption indices rise gradually with increasing temperature. The absorption edge moves forward to the short wavelength infrared from about 3.5 µm at 300 K to about 2.75 µm at 1800 K.